Culinary Tourism in Central America: A Cross-Analysis of Government Tourism Websites. Issue 3 (3rd July 2018) - Matwick, Keri; Matwick, Kelsi
ABSTRACT: Food and beverage are growing tourism niches and have yet to realize their potential in Central America. This study explores how culinary tourism is promoted in official tourism websites of Honduras, Costa Rica, Guatemala, El Salvador, Nicaragua, and Panama. Through a qualitative content analysis, this study examines how the websites introduce and promote traditional and local foods, restaurants, culinary tours, food festivals, recipes, and food safety. This study assesses the culinary tourism marketing strategies, including text and image, and provides practical suggestions for promoting food-related information through these platforms.